Internet of things evolution: A European perspective - Oliveira e Sá, Jorge (2019)
Since 2009, the European Union (EU), through the IoT European Research Cluster (IERC), publishes Strategic Research Agendas (SRA) with short, medium and long term forecasts of development and research topics about the Internet of Things (IoT). The aim of this paper is to study the SRAs published since 2009 and, based on an extensive analysis and review, to make an identification of the relevant topics in the realm of IoT, in order to understand their evolution over time. This study involves the SRAs of 2009, 2011, 2014, 2015, 2016 and 2017. We are particularly interested in understanding the IoT technology development efforts over this period of almost a decade and the research areas that have already been explored, as well as those that have not received attention yet. In simple words, we aim to conclude about the dynamics of the IoT field in Europe and its probable evolution path